APLIKASI KONSEP MANAGING FOR RESULTS - Jurnal Governance Jurnal Kebijakan & Manajemen Publik; AGUS WAHONO (FISIP UWP, 2010)
State government in the United States have enthusiastically embraced the idea of managing for result. This appears to represent the victory for New Public Management policy ideas transferred from New Zealand, the United Kingdom, and Australia. The managing for result doctrine that emerged from these countries called for an increased focus on results but also increased managerial authority to achieve results. In turn, it was claimed, government would enjoy dramatic performance improvement and result-based accountability. This article assess the implementation of public management reform and argues that the managing for results doctrine has benen only partially adopted. State governments selected some of the New Public Management ideas but largely ignored others. In short, state government emphasized strategic planning and performance measurement but were less successful in implementing reforms that would enhance managerial authority, undermining the logic that promised high performance improvements.